Postoperative Deep Sedation after Microvascular Reconstructive Surgery for Oral Cancer Increases the Risk of Early Postoperative Pneumonia - Satoshi Fukuzawa; Kenji Yamagata; Shohei Takaoka; Fumihiko Uchida; Naomi Ishibashi-Kanno; Toru Yanagawa; Hiroki Bukawa (Dentistry Journal, 2023)
This study investigated the effect of postoperative deep sedation after oral cancer reconstructive surgery on the occurrence of early postoperative pneumonia and early postoperative delirium. We obtained medical records of 108 consecutive patients who underwent microvascular reconstructive surgery at Tsukuba University Hospital for oral cancer between January 2013 and December 2021. Forty-six of them woke soon after surgery. Ten of these forty-six patients were restless and required immediate sedation within 3 h after surgery. The comparison between sedation group and no sedation group revealed early postoperative pneumonia in the no sedation group; however, sedation was not related to early postoperative delirium. The preoperative albumin levels of patients with postoperative pneumonia were significantly different (p = 0.03) than those of patients without postoperative pneumonia. The performance status (p = 0.02), preoperative albumin level (p = 0.02), and age 75 years or older (p = 0.02) were significantly associated with postoperative delirium. Restless patients and those who could not be sedated experienced delirium and pneumonia. The risk of pneumonia was increased for patients who were difficult to sedate.